Antifungals : From Genomics to Resistance and the Development of Novel Agents. - Coste, Alix T.; Vandeputte, Patrick (Caister Academic Press, 2015)
Infections caused by pathogenic fungi are a significant global problem; a situation exacerbated by the limited availability of good antifungal options. Being eukaryotic organisms, these pathogens are phylogenetically much closer to the human host than bacterial pathogens. This sets serious limits to the range of exploitable fungal-specific drug targets. The advent of 'omics' and other high throughput technologies in recent years has revolutionized the field of antifungal research permitting researchers to quickly identify novel compounds and gain greater insights into drug resistance mechanism.